Is CK-MB isoenzyme useful for diagnosis of cardiac involvement in icteric leptospirosis? - Machado, Elizabeth Stankiewicz; Feres, José Guilherme de Faria; Feijó, Luis Augusto; Andrade, Jarbas; Nogueira, Susie Andries (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
In the absence of heart failure or cardiogenic shock, cardiac involvement diagnosis in icteric leptospirosis is possible on the basis of abnormal electrocardiograms. As metabolic and electrolytic disorders are frequently seen during acute leptospirosis infection, they may be responsible for some electrocardiograms changes. We conducted a study to assess if creatine phosphokinase isoenzyme determinations are useful in selecting patients with a high cardiac involvement suspicion. Sixty-nine patients were studied prospectively. Ten patients out of 16 with cardiac involvement and 25 without had high CK-MB levels (p>;0.05), although mean values of abnormal CK-MB levels were higher in the group with cardiac involvement (p